Professor Andrzej Stepnowski - SALAMON, Roman (Archives of Acoustics, 2024)
Professor Andrzej Stepnowski was born in Biała Podlaska on 4 January 1940, the son of a lawyer couple who settled in Gdansk after the war. Between 1958 and 1964, he studied at the then Faculty of Communications of Gdansk University of Technology, and was a prominent member of the board of the Polish Students’ Association. In 1964, he earned his master’s degree in electronics with a focus on radiolocation, and became an assistant at the Department of Radionavigation, where he conducted hydroacoustics research.